Berbagai upaya Azif Ali Zardari menyelesailakan masalah keamana pasca memenangkan pemilu Pakistan 2008 - Indri Astuti (2010)
Berbagai upaya Azif Ali Zardari menyelesailakan masalah keamana pasca memenangkan pemilu Pakistan 2008